I wonder why kangaroos have pouches : and other questions about baby animals - Wood, Jenny (Danbury, Connecticut : Grolier Inc, 1999)
I Wonder Why Trees Have Leaves is jam-packed with fascinating facts about baby animals, from 'Which is the biggest baby in the world?' to 'When does a tiger cub leave home?'
Includes index
Keywords: Science